Apathy Syndrome in Neurological Diseases – State of the Art and Current Research Directions - Roessler-Górecka, Magdalena (Przegląd Psychologiczny, 2024)
Aim: Apathy is sometimes indicated as a symptom in various diseases, among others in psychiatry. However, for several decades it has also been distinguished as an independent syndrome accompanying many neurological diseases. Although still omitted from current medical classifications, apathy syndrome is the subject of numerous theoretical and clinical analyses. The spreading of knowledge on it among clinicians – including the possibility of recognizing and differentiating it, especially from depression – is of fundamental importance for the effectiveness of therapeutic interventions. The paper presents definitions and diagnostic criteria of apathy syndrome proposed in the literature. It presents data on its prevalence in various diseases, its relationship with brain pathology, and several clinical variables. Theses: Contemporary concepts emphasize the syndromic character, multidimensionality of apathy syndrome and links with the broadly understood functions of frontal lobes. The domains of functioning in which symptoms of apathy may be revealed include the cognitive sphere, the emotional sphere, social interactions, and behavior (initiating and maintaining any intentional activity). The relative independence of apathy syndrome from depression is indicated, the importance of apathy syndrome as a prognostic factor for dementia is emphasized, as well as its relationship to quality of life, effectiveness of rehabilitation and psychological burden on caregivers. As for neuronal basis of apathy, a few partially overlapping processes are considered, with significant role of basal ganglia and certain areas of prefrontal cortex. Conclusion: Dysfunction of any link of complex prefrontal-subcortical circuits may be crucial for occurrence of apathy symptoms, which explains high frequency of this syndrome in brain diseases, especially those with damage to basal ganglia and/or prefrontal cortex. Different severity of symptoms in particular domains and recurrence of abnormality profiles observed depending on the analyzed disease and/or location of brain pathology prompt the search for subtypes of apathy syndrome.